Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3126/jnhrc.v15i2.18202
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Pre-peritoneal Mesh Repair versus Lichtenstein’s Hernioplasty

Abstract: Background: In the era of minimal invasive surgery, hernia repair has seen a paradigm shift from open to laparoscopic technique. However, superiority of laparoscopic repair over open repair is still controversial. Available literatures have shown laparoscopic technique to be better in term of post-operative pain and early return to work.Methods: In this prospective study, a total of 102 patients aged 21-78 years with inguinal hernia were recruited and enrolled into two comparative groups, namely Lichtenstein’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 7 publications
0
15
0
4
Order By: Relevance
“…31 While Koju et al reported a significant difference in pain score with low pain score in TAPP group was seen to be (2.00±0.63 versus 3.90±0.73, p<0.001). 33 Also Garg et al reported that at 0, 12, 24 and 72 hours postoperatively, LH patients described significantly less pain than the open group (p<0.05). 32 Although the visual analogue scale (VAS) pain scores of the LH group were also lower than the OH group on postoperative day 14, these differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…31 While Koju et al reported a significant difference in pain score with low pain score in TAPP group was seen to be (2.00±0.63 versus 3.90±0.73, p<0.001). 33 Also Garg et al reported that at 0, 12, 24 and 72 hours postoperatively, LH patients described significantly less pain than the open group (p<0.05). 32 Although the visual analogue scale (VAS) pain scores of the LH group were also lower than the OH group on postoperative day 14, these differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 94%
“…Also Our results differ from those of Koju et al who reported that there were two wound infections and one seroma formation in conventional group whereas in TAPP group there were three recurrence (one after 3 months, one after 2 weeks and one after one year of surgery) and one conversion due to adhesion. 33 . Whereas Shah et al found in his study, that the mean period of hospitalization was slightly higher 3.5 days in case of laparoscopic hernia repair with 3.23 days in cases of hernioplasty but not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Основные преимущества лапароскопического доступа -это ранняя реабилитация, гладкое течение раннего послеоперационного периода, возможность выполнения одновременной двусторонней пластики, в том числе при бессимптомной грыже [1,3].…”
unclassified